Spherical nucleic acids : the foundation for crystal engineering with DNA and digital probe and drug design - Mirkin, Chad A. (Singapore : Jenny Stanford Publishing, 2020)
Spherical nucleic acids (SNAs) comprise a nanoparticle core and a densely packed and highly oriented nucleic acid shell, typically DNA or RNA. They have novel architecture-dependent properties that distinguish them from all other forms of nucleic acids and make them useful in materials synthesis, catalysis, diagnostics, therapeutics, and optics/plasmonics. This book covers over two decades of Dr. Mirkin's research on SNAs and their anisotropic analogues, including synthesis and fundamental properties, and applications in colloidal crystallization, adaptive matter, and nanomedicine, spanning extra- and intracellular diagnostics, gene regulation, and immunomodulation. It is a reprint volume that compiles 101 key papers from high-impact journals in this research area published by the Mirkin Group at Northwestern University, Illinois, USA, within the International Institute for Nanotechnology, and collaborators. Volume 1 provides an overview and a historical framework of engineering matter from DNA-modified constructs and discusses the enabling features of nucleic acid-functionalized nanomaterials. Volume 2 covers design rules for colloidal crystallization, building blocks for crystal engineering, and DNA and RNA as programmable bonds. Volume 3 discusses colloidal crystallization processes and routes to hierarchical assembly, dynamic nanoparticle superlattices, surface-based and template-confined colloidal crystallization, optics and plasmonics with nanoparticle superlattices, and postsynthetic modification and catalysis with nanoparticle superlattices. Volume 4 covers diagnostic modalities, and intracellular therapeutic and diagnostic schemes based upon nucleic acid-functionalized nanomaterials.
OCLC-licensed vendor bibliographic record.
Keywords: Nucleic acids; RNA -- Synthesis; DNA -- Synthesis; Nanochemistry; Drug development; SCIENCE / Biotechnology